КЕРУВАННЯ ПОЛОЖЕННЯМ НЕДОРОГИХ БЕЗРЕДУКТОРНИХ ПРИВОДІВ НА БАЗІ ЯВНОПОЛЮСНИХ СИНХРОННИХ ДВИГУНІВ З ПОСТІЙНИМИ МАГНІТАМИ - Пересада, С.М.; Родькін, Д.І.; Ніконенко, Є.О.; Ковбаса, С.М.; Поліщук, В.В. (Інститут електродинаміки НАН України, Київ, 2023)
Torque ripple compensation problem is considered for electrical drives, based on low-cost direct drive interior permanent magnet synchronous motors. Robustness properties of the speed and position control systems have been studied using time scale separation properties of the current, speed and position control loops. It is shown that system closed-loop dynamics according to new controller design has cascaded properties with speed and position control loops connected in series and therefore has potential of high frequency torque ripple compensation by increasing controller’s gains. Experimental results are presented for two motors with similar rated data but significantly different level of the torque ripple. It is shown that despite of significand difference in parasitic torque amplitude, the similar position control performance can be achieved. It makes proposed control algorithms suitable for both high dynamic performance and low-cost direct drive applications with medium performance requirements. References 13, figures 7.